Analysis of large bandgap dielectrics by dual plasmon-photon excitation. (20th April 2020) - Berco, Dan; Ang, Diing Shenp
Abstract: This work demonstrates a non-destructive approach that uses low-energy radiation in conjunction with low-voltage electric bias to analyze deep defect states in large bandgap dielectric materials. The method is based on a double electronic excitation process, where visible light is employed to energize electrons to overcome, an otherwise too large, band-gap barrier. It is demonstrated over a nanometer-sized, semiconductor-insulator-metal (transparent top electrode, large bandgap dielectric, metallic bottom electrode) test structure. During the measurements, hot-electrons are produced at the transparent electrode by irradiating a plasmonic probe (i.e. Au). These energetic electrons are then transported to the top electrode-dielectric interface, where the same radiation excites them over the energy barrier. This two-step process results in a photocurrent that allows charge to occupy dielectric defect states via relaxation. Furthermore, introducing a non-overlapping time shift between photonic and voltage pulse stimulations is shown to produce a 'load and shoot' effect. In this manner, some defect states are preset prior to illumination thus affecting the photocurrent pattern. An analysis of defect density is then performed by spectral decomposition of this spatiotemporal pattern.